Radiological Risk Assessment of Technologically Enhanced Naturally Occurring Radioactive Materials in coal wastes from Van Eck Coal-Fired thermal Power Plant, Namibia. - Hitila, Markus V.; Onjefu, Sylvanus A. (Namibian Journal for Research, Science and Technology, 2022)
In this study, the radioactivity concentrations and the potential radiological health hazards of primordial radionuclides; 226Ra, 232Th and 40K were measured using coaxial high-purity germanium (HPGe) gamma detector in coal, bottom and fly ashes collected from a 120 MW Van Eck thermal power plant, Windhoek, Namibia. The experimental results showed that for coal samples, the activities of 226Ra, 232Th and 40K were 20.22 ± 3.82 Bq/kg, 26.70 ± 5.90 Bq/kg and 30.36 ± 6.36 Bq/kg, respectively. For ashes samples, the activities of 226Ra, 232Th and 40K were 88.89 ± 11.91 Bq/kg, 113.28 ± 15.44 Bq/kg and 97.84±16.55 Bq/kg, respectively for bottom ash and 59.18 ± 4.55 Bq/kg, 77.00 ± 5.89 Bq/kg and 77.17 ± 7.30 Bq/kg, respectively for fly ash. The activity concentration of 226Ra, 232Th and 40K were all enhanced in the bottom and fly ash relative to coal samples. However, the estimated radiological health hazards and the concentration of the various samples from the selected location were within the permissible limits provided for human safety and environmental protection.